Participatory Audiovisual: Convergence between Communication and Environment - Ramírez Rueda, Angie Tatiana (2020)
This article presents various reflections on the use of participatory audiovisuals as a tool that mobilizes communities towards other forms of communication, where collaborative work is valued in order for them to be the creators of their own content, and thus rethink their territories. Taking this premise as a starting point, theeducommunicative strategy, “Pescando historias. Memorias de un llanitero” (Memories of a Llanitero) was developed with adolescents and young people from Corregimiento el Llanito in Barrancabermeja, Colombia, who were trained in audiovisual production with an emphasis on the environment. The methodology implemented was qualitative, from the line of action research (IA), thus providing spaces for participation and dialogue with young people. This research was based on educommunication during the pedagogical training from a critical perspective to strengthen the discourses and environmental practices of the participants, at the same time that they were trained in the use of this communicative tool.